Organic Management Affects Growth, Yield, Quality and Soil Properties in Elephant Foot Yam - Kolambe, B. N; Patel, K. G; Kaswala, A. R; Patel, V. S; Desai, K. D (JOURNAL OF ROOT CROPS, 2014)
A field experiment was conducted at the Organic Farming Unit, Navsari Agricultural University, Navsari, during 2010-2011 and 2011-2012 to study the growth, yield and quality of elephant foot yam and soil properties as affected by organic manures and biofertilizers under organic farming. Ten treatments were evaluated in this experiment; among them nine were different combinations of organic manures, ash and biofertilizers and one INM treatment . (FYM @ 10 t ha-1 + NPK @ 80:60:100 kg ha-1) was studied outside the organic farm. These treatments were tested in randomized block design with three replications. Among the different treatments, the INM treatment, FYM @ 10 t ha-1 + NPK @ 80:60:100 kg ha-1 resulted in higher crop growth and tuber yield followed by the organic treatment, vermicompost @ 5 t ha-1 + Azospirillum @ 5 kg ha-1 + phosphorus solubilising bacteria (PSB) @ 5 kg ha-1 + ash @5 t ha-1 during all the years. The soil organic C content also increased significantly due to the application of organic manures, whereas soil physical and chemical properties were unaffected. The economic analysis indicated that the INM treatment resulted in the highest net income of ` 2,90,000 ha-1 (BCRof 2.9) followed by the organic treatment, vermicompost @ 5 t ha-1 + Azospirillum @ 5 kg ha-1 + PSB @ 5 kg ha-1 + ash @ 5 t ha-1 (net income of ` 2,56,000 ha-1; BCR of 2.6).